Blotch - Husin, Muhammad; Musa, Muhammad Zamuren; Azizi, Mohd Khair (2010)
Snatching issue in Malaysia has becoming serious recently. The primary safety that is a concern is lives of the victims. Their valuable things come later. BLOTCH is an anti-snatch handbag that will ensure the safety of the victims first before their belonging. The strips of the handbag will detach once snatched by the snatch thief. After that it will launch the airbag and all the belongings will fall on the ground. In a rushing situation, the snatch thief will tend to run away with an empty handbag or leave the handbag at the place of incident. Consequently, this ensures the safety of the victims and his belongings will be intact.